CXCR3 blockade combined with cyclosporine A alleviates acute graft-versus-host disease by inhibiting alloreactive donor T cell responses in a murine model. (February 2018) - Miao, Shengchao; Tang, Bo; Liu, Huihui; Wang, Zhenhua; Shi, Yongjin; Dong, Yujun; Liu, Wei; Qin, Chenchen; Ren, Hanyun
Highlights: CXCR3 antagonist together with CsA had a synergy effect to mitigate aGvHD in a murine aGvHD model. The mechanism relied on inhibiting of donor-derived T cell responses. AMG487 combined with CsA decreased the oncentrations of pro-inflammatory cytokines in serum. Abstract: Chemotaxis of T cells to acute graft-versus-host disease (aGvHD) target tissues directed by chemokines and their receptors plays a key role in the pathogenesis of aGvHD. Blockade of lymphocyte migration by targeting chemokine receptors may be a viable strategy for the prevention and treatment of aGvHD, which is quite distinguishable from typical efforts to use immunosuppressive medications that have been associated with some side effects. CXCR3 and its ligands have been reported to be correlated with aGvHD pathogenesis. Using the small-molecule CXCR3 antagonist AMG487, we demonstrated that AMG487 combined with cyclosporine A (CsA) effectively alleviated aGvHD with a prolonged mean survival time and significantly inhibited the infiltration of inflammatory cells in aGvHD target tissues in a murine aGvHD model. In addition, AMG487 combined with CsA inhibited the activation, proliferation and differentiation of donor-derived T cells in the spleens. Further results showed that the concentrations of Th1 cells associated with pro-inflammatory cytokines such as IFN-γ and TNFα in serum were decreased. In addition, AMG487 treatment did not alter CXCR3 and CCR5 expression in donor-derived T cells but elevated the serum CXCL9 and CXCL10 levels. This novel and effective approach has the potential to develop a new clinical method to prevent and treat aGvHD.